2012
DOI: 10.5005/jp-journals-10015-1119
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antimicrobial Solutions on Streptococcus mutans in used Toothbrushes

Abstract: Purpose:The objective was to determine the effectiveness of antimicrobial solutions on Streptococcus mutans in used tooth brushes.Methods: Sixty children used their toothbrushes twice a day, for seven consecutive days. The toothbrush bristles were then immersed into antimicrobial solutions for 12 hours: Group I-3% neem; group II-5% turmeric; group III-0.5% cetylpyridinium chloride, group IV-0.2% chlorhexidine gluconate. They were then placed into test tubes containing the resultant suspensions were three-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Curcumin mouth rinse may be dependent upon several factors, including duration of fasting 28 and time of mouth rinse. 38 Although there is a growing number of publications about the effect of curcumin on bacterial reduction, 16,18,28,39,41 few publications 28,39 such as this study observed the magnitude of curcumin as a mouth rinse.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Curcumin mouth rinse may be dependent upon several factors, including duration of fasting 28 and time of mouth rinse. 38 Although there is a growing number of publications about the effect of curcumin on bacterial reduction, 16,18,28,39,41 few publications 28,39 such as this study observed the magnitude of curcumin as a mouth rinse.…”
Section: Discussionmentioning
confidence: 72%
“…In an in vitro model, Hegde and Kesaria 17 showed that curcumin reduced only C. albicans, and that sodium hypochlorite and neem (Azadirachta indica) were more effective in microbial inactivation, because it reduced both E. faecalis and C. albicans. In a clinical trial, Bhat et al 16 showed that the antimicrobial efficacy of neem (3%) was highest, followed by cetylpyridinium chloride (0.5%), curcumin (5%), and chlorhexidine gluconate (0.2%) when the CFU (S. mutans) reduction was measured. Chlorhexidine is widely used in dentistry for decontamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial properties of neem plants have been demonstrated by Bhat et al, wherein antibacterial solutions containing neem had the highest effectiveness in reducing the number of S. mutans when compared with turmeric, chlorhexidine, and cetylpyridinium chloride [17]. However, further studies evaluating the effectiveness of herbal toothpastes containing neem leaf extracts in larger samples with severe gingival inflammation over a longer time frame are warranted.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings with CHX solutions are in accordance with the results of Bhat et al . [ 18 ] and Balappanavar et al . [ 11 ] though both of the studies assessed only the reduction of S. Mutans count after disinfecting with CHX solution.…”
Section: Discussionmentioning
confidence: 99%